Sujeto liberal y patologías sociales - Pereira, Gustavo (2008)
“Liberal Subject and Social Pathologies”. This work presents thelimits of the idealization of the liberal subject. Its distinctive characteristics, which make this subject one that is scarcely vulnerable to circumstances and assume the possibility to evaluate ends and preferences, limit the awareness of phenomena of colonization of the world of life. Only by modifying such idealizationthrough deep self-reflection shall these colonizing phenomena be overcome. On the other hand, this new type of subject shall be able to participate in the relevance of personal behaviour as regards consumerism and the applicability of principles of justice.